A Kuka de Kamaiorá ou O Segredo da Alma D'ouro: metaficção historiográfica, 1973-1983 - Alves, Júnia de Castro Magalhães (Aletria: Revista de Estudos de Literatura, 1995)
This essay analyses Leilah Assunção's post-modern play, a Kuka de Kamaiorá, which was written in 1973 but only staged ten years later. A careful reading of the dramatic text reveals some ideological confrontation among different sociopolitical strata in Brazil.